PENGARUH RELIABILITY, PERFORMANCE, FEATURES, CONFORMANCE, DURABILITY TERHADAP PURCHASE DECISION - Indrawan Wijaya, Hartono; Immanuel, Dewi Mustikasari (Universitas Ciputra Surabaya, 2023)
This study aims to know the effect of the effects of the five dimensions of product quality on consumer chemicals purchase decisions of CV. Prasida Jaya. Multiple Linear Regression analysis of SPSS has been used in this study, the population in this study are consumers who have purchased chemicals at CV. Prasida Jaya. Samples were taken using the purposive sampling method with a total of 37 samples. Data collection in this study was carried out by distributing online questionnaires to respondents. The results of this study found that reliability, performance, features, conformance, and durability have a positive and significant effect on purchase decisions. Based on the t-statistic value testing that has been done, it is known that reliability (t-statistic value = 0.009), performance (t-statistic value = 0.004), features (t-statistic value = 0.023), conformance (t-statistic value = 0.015), and durability (t-statistic value = 0.004) has a positive and significant effect on purchase decisions. Based on the conditions above, it can be concluded that the higher product quality, it will increase the purchase decision for chemicals at CV. Prasida Jaya. Keywords: reliability, performance, features, conformance, durability, purchase decision